Urgensi Pengawasan Praktik Nominee Arrangement Dalam Perjanjian Joint Venture Di Indonesia - Victoria Tabita (Jurnal Relasi Publik, 2023)
The practice of the Nominee Agreement, which involves an agreement between the legal shareholder and the beneficiary, is often the method used for shareholding in limited liability companies, especially Joint Ventures. In this agreement, the registered shareholder (nominee) is the shareholder, while the beneficiary is the party who actually controls and receives direct benefits from the company. Even though this practice is expressly prohibited in foreign investment in Indonesia, especially based on Article 48 UUPM, and the agreement can be canceled by law because it does not meet the requirements of a legal cause in accordance with Article 1338 Paragraph (1) of the Civil Code, the use of nominee shareholders has not been prohibited explicitly by the government. Therefore, this can be considered as an attempt to circumvent the law or an act of legal manipulation. The type of research used in this study is empirical research, which includes research on legal identification and research on legal effectiveness.